1990
DOI: 10.1136/bmj.300.6721.363
|View full text |Cite
|
Sign up to set email alerts
|

Risks of acute traumatic intracranial haematoma in children and adults: implications for managing head injuries.

Abstract: Objective-To determine the factors influencing the risk of an acute traumatic intracranial haematoma in children and adults with a recent head injury.Design-Prospective study of incidence of risk factors in samples of patients attending accident and emergency departments and in all patients having an acute traumatic intracranial haematoma evacuated in one regional neurosurgical unit during 11 years.Setting-Accident and emergency departments in Scotland or Teesside and regional neurosurgical centre in Glasgow.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1
8

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(121 citation statements)
references
References 29 publications
4
107
1
8
Order By: Relevance
“…This study found that .017% of cases with a GCS score of 15 required surgery. 10 We conclude from these data that:…”
Section: Risk Of Intracranial Injurymentioning
confidence: 85%
“…This study found that .017% of cases with a GCS score of 15 required surgery. 10 We conclude from these data that:…”
Section: Risk Of Intracranial Injurymentioning
confidence: 85%
“…26) The presence of fracture was only assessed in 59% of our patients, but had a strong influence on intracranial lesions, as previously reported. 5,11,25,31) However, which patients should undergo skull radiography, and timing are unclear. Although the presence of fracture increases the likelihood of intracranial lesion, the sensitivity of skull radiography is not high enough to be a useful screening test, 8,12) as confirming the absence of fracture does not rule out intracranial injury.…”
Section: Ct Indications In Mild Head Injurymentioning
confidence: 99%
“…Skull radiographs have been used as part of the evaluation for children with head trauma, yet their value remains controversial. [11][12][13] Head computed tomography (CT) has become the diagnostic method of choice for identification of intracranial disorders in patients with head trauma. 14 However, CT is expensive, not always readily available, sometimes requires sedation of the patient, and always requires skilled interpretation.…”
mentioning
confidence: 99%